Réponses

2012-11-11T20:05:25+01:00

a) 5x-((4x)*-2x4x X 2+ 2*

5x - ( 16 x* - 16x +4 )

5x -16x* +16x -4

et tu calcules

2012-11-11T20:14:08+01:00

a) 5x-(4x-2)^2 

=5x - (4x-2) X (4x-2)

=5x - (16x^2-8x-8x+4)

= 5x-(16x^2-16x+4)

= 5x-16x^2+16x-4

= -16x^2+21x-4

 

b) (2x+4) (9-5x) -(1-3x)^2

= (18x-10x^2+36-20x) - (1-3x) X (1-3x)

= (-10x^2-2x+36) - (1-3x-3x+9x^2)

= -10x^2-2x+36 - (9x^2-6x+1)

= -10x^2 -2x +36 -9x^2 +6x -1

-19x^2+4x+35

 

^2 = au carré

Voila en espèrant tavoir aidée !

:)